Corporate Social Responsibility (CSR) Application of PT. Sido Muncul, Tbk for Improving Community Welfare In Education - Tirta Wangi, Putri Ayu; Riyanto, Setyo; Diarta, Luthfita Ayu (Syntax Idea, 2021)
Corporate Social Responsibility (CSR) is an awareness and understanding of the company that is obtained directly or indirectly as one of the important things to be maximized because of the great reputation benefits obtained from the company's CSR activities. CSR is a business commitment so that companies act ethically in running operations legally and contribute to improving the welfare of company employees, local communities, and the wider community. In the literature study, it was found that the benefits will be obtained for the company and the surrounding community.